2016
DOI: 10.1111/vsu.12485
|View full text |Cite
|
Sign up to set email alerts
|

Scintigraphic Tracking of Allogeneic Mesenchymal Stem Cells in the Distal Limb After Intra‐Arterial Injection in Standing Horses

Abstract: Intra-arterial injection of MSC can be performed in standing horses under sedation and successfully distribute MSC to the distal limb. A risk of periarterial injection was identified but can be reduced with proper sedation, local anesthesia, and increased experience. Partial venous thrombosis was observed as a complication, but did not cause changes of clinical importance, other than rare transient swelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
(45 reference statements)
1
11
1
Order By: Relevance
“…In horses, partial venous thrombosis (typically subclinical) has been observed following regional i.a. catheterisation [165,166]. Another study showed severe arterial thrombosis following tourniquet application and i.a.…”
Section: Intra-arterialmentioning
confidence: 99%
See 2 more Smart Citations
“…In horses, partial venous thrombosis (typically subclinical) has been observed following regional i.a. catheterisation [165,166]. Another study showed severe arterial thrombosis following tourniquet application and i.a.…”
Section: Intra-arterialmentioning
confidence: 99%
“…catheterisation [165,166]. Tourniquet use was thought to be the cause and more recent studies without the tourniquet report no severe complications [165,166,168]. delivery of mesenchymal stem cells that caused severe lameness and dermal necrosis [167].…”
Section: Adverse Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSCs were labelled as previously described [10]. Briefly, hexamethylpropyleneamine oxime (HMPAO) k was solubilised in 20 lL Dimethyl sulfoxide (DMSO) l and then diluted to 125 lg/mL with sodium chloride injection solution.…”
Section: Mesenchymal Stem Cell Labeling Techniquementioning
confidence: 99%
“…Intra-arterial injections without a tourniquet resulted in better distribution and better persistence of the MSCs compared with intravenous regional limb perfusion [9]. Intraarterial injections of the front limbs were initially performed under anaesthesia but a technique has now been established in the standing horse [10,11]. This technique is now used for treatment of soft tissue lesions from the level of the suspensory origin to the distal limb.…”
Section: Introductionmentioning
confidence: 99%